Exploration of Artificial Intelligence Assisted Software Development Process Automation Technology - Lin, Jun (International Journal of Computer Science and Information Technology, 2024)
By systematically analyzing the application status of artificial intelligence (AI) technology in the field of software development, this article reveals its positive role in improving development efficiency, reducing costs and promoting industry innovation. Futhermore, it also points out the problems that need to be solved urgently, such as the change of employment market, ethical and legal challenges and technical security. By combing the relevant literature, this article summarizes the historical evolution and present situation of AI-aided software development, and probes into its socio-economic impact and ethical and legal issues. Finally, considering the actual situation, this paper puts forward the countermeasures that the government, enterprises and educational institutions should use. The results show that AI-aided software development brings great opportunities and a series of challenges. In order to meet these challenges, some measures are put forward, including strengthening policy guidance, perfecting education system, establishing industry standards and ethical standards. AI-aided software development is the inevitable trend of the future development of the software industry, but it needs to find a balance between technological progress and social responsibility. With the joint efforts of all parties, it is possible to realize the deep integration of AI technology and software development.